Comparative Study of Ramayana Legend Story Performance as a Tourist Attraction in Prambanan, Purawisata, and Uluwatu - Intan Nurmala Fadin, Delfyan (Ann Publisher, 2023)
The Ramayana Legend Show is one of the popular tourist attractions in Indonesia. This study will present a comparison of the presentation of the Ramayana Legend Story performance at Prambanan Temple, Purawisata Jogja and Uluwatu Bali. The purpose of this study is to understand the difference between the two tourist attractions. The method used in this study is qualitative descriptive with comparative studies. Data collection is carried out through observation, interviews, and literature studies. The results showed that there were differences in appearance, acculturation with local culture, quality of performance, and overall experience for tourists at Prambanan Temple, Purawisata and Ulu Watu Bali. Attractions use the open stage of Prambanan Temple, Mandira Baruga in Purawisata and Ardha Candra Cultural Park in Ulu Watu, Attractions in Prambanan Temple use gamelan with modern lighting, Purawisata uses gamelan combination technology and background lights, while in Uluwatu the sound is only from the voice of the Cak-cak-cak Dancer and clarified by the voice of a Dalang.